The United States' Role in Peace Negotiations Between Israel and Palestine: Examining Achievements, Setbacks and Difficulties - Aissaoui salsabil; Hamied Bouchra; Chetehouna Nadjla (University of Eloued جامعة الوادي, 2025)
ملخص الدراسة: تسعى هذه المذكرة الى دراسة نقدية للدور المتعدد الأوجه الذي اضطلعت به الولايات المتحدة الأمريكية في مفاوضات السلام بين إسرائيل وفلسطين منذ عام 1948 وحتى الوقت الراهن. و تستعرض المسار التاريخي للمشاركة الدبلوماسية الأمريكية، وتُبيّن أبرز الإنجازات والإخفاقات المتكررة و كذلك التحديات المستمرة التي ميزت هذا الدور. كما تسعى إلى تحليل الدوافع الكامنة وراء السياسة الأمريكية، بما في ذلك المصالح الجيوسياسية خلال الحرب الباردة وما بعدها، مع تقييم تأثير الإدارات الأمريكية المتعاقبة على مسار عملية السلام . تتطرق المذكرة إلى أبرز المبادرات الدبلوماسية الرئيسية مثل اتفاقيات كامب ديفيد، ومؤتمر مدريد، واتفاقيات أوسلو، وجهود ما بعد عام 2000 بما في ذلك "خارطة الطريق للسلام" وسياسات إدارات أوباما وترامب وبايدن. كما تسلط الضوء على كيف أن الانتفاضة الثانية ، والتوسع الاستيطاني الإسرائيلي المستمر، وديناميكيات القوى الإقليمية ، والانقسامات الفلسطينية الداخلية التي شكلت عقبات كبيرة أمام تحقيق حل مستدام للقضية. وتخلص الدراسة إلى أن الولايات المتحدة، رغم كونها فاعلًا دبلوماسيًا محوريًا، لم تنجح في تقديم تسوية عادلة ومستدامة للصراع، نتيجة انحيازها الظاهر في بعض الفترات، وافتقار سياساتها للثبات والتوازن المطلوبين. وبناءً عليه، توصي المذكرة بضرورة إعادة هيكلة النهج الأمريكي تجاه القضية، عبر تبنّي سياسة أكثر حيادية واتساقًا، قد تشمل تعاونًا دوليًا أوسع، بما يعزز فرص تحقيق سلام عادل ودائم بين الطرفين. Abstract Covering the years 1948 until the present, this dissertation provides a critical examination of America's multilateral role during peace negotiations between Israel and Palestine. The primary purpose is to assess the successes, failures, and disappointments which have guided American mediation. Utilizing historical and analytical methods, the research utilizes a qualitative study design guided by policy briefs, official declarations, UN decisions, and scholarly literature. The research conclusions indicate that while the U.S. has performed an invaluable role of a mediator, its strategic alliance with Israel has always worked against its neutrality and detracted from its capacity to exert evenly balanced pressures on both parties. Bilateral achievements such as the Camp David Accords and Israel-Jordan Peace Treaty were quite bilateral and never addressed the key issues of the Israeli-Palestinian conflict i.e., borders, Jerusalem, settlements, refugees, and security. Concurrently, failures were routinely associated with erratic policies, political diplomacy, and weak enforcement. The dissertation concludes that American diplomacy has primarily held back but not resolved the conflict at the expense of long-term justice in favor of short-term stability. It demands a rebalanced American strategy with an anchor in multilateralism and international law. Subsequent research could analyze different mediation models and quantify the influence of U.S. domestic interest groups on Middle East policy.
Master's Degree In Literature and Civilization
Keywords: الصراع الإسرائيلي الفلسطيني، السياسة الخارجية الأمريكية، عملية السلام في الشرق الأوسط، الدبلوماسية، الوساطة الدولية، اتفاقيات كامب ديفيد; Camp David Accords; Israeli-Palestinian Conflict; Mediation; Middle East Peace Process; U.S. Foreign Policy.